Common Good, God, and Human Rights - A Reflection on "We Choose Abundant Life" - Gunner, Göran (Review of ecumenical studies, 2025)
This article addresses watchwords that are dealt with in We Choose Abundant Life in relation to human rights. Speci"cally addressed are: the right to life and abundant life, the minority concept, vulnerable groups, freedom of conscience in relation to freedom of religion or belief and the idea of a crown among freedoms. The question is raised about in what way human rights may be a useful tool for theology and religious communities. The concept of "common good" is used to discuss how theology with the expression kingdom of God and a society based on democracy, equal citizenship and human rights are speaking the same language. One conclusion is that the document, through its working method, analysis, conclusions and recommendations, has to develop choices and policies for a common good based on theology in combination with human rights and democracy.